IMPLEMENTASI PENDIDIKAN KRISTEN BERDASARKAN AMSAL 3 DI ANTARA MAHASISWA SEKOLAH TINGGI TEOLOGI DI SURABAYA - Suryaningsih Soepardi (Sekolah Tinggi Teologi Excelsius, 2020)
Abstract: Christian education is education based on the Word of God. The objectives of this study were: (1) To find out to what extent the tendency of the implementation of Christian education based on Proverbs 3 among the students of the Theology College in Surabaya. (2) To find out which dimension is dominant for the implementation of Christian Education based on Proverbs 3 among Students of Theological College in Surabaya. (2) Finding out which background is dominant in the implementation of Christian Education based on Proverbs 3 among Theological College Students in Surabaya. This study uses an explanatory-confirmatory approach. The research subjects were all students of the Theological College in Surabaya with a total of 60 students. The technique of taking the population uses